Present beyond measure : design, visualize, and deliver data stories that inspire action - Pica, Lea (Newark : John Wiley & Sons, Inc, 2024)
Are you suffering from Data Presentation Zombification? Billions of dollars and thousands of hours are lost every year during ineffective business meetings worldwide. Data practitioners painstakingly present their valuable analytical insights, only to fall flat, inspiring more yawns than yeses. In Present Beyond Measure: Design, Visualize, and Deliver Data Stories That Inspire Action, Lea Pica provides a 4-phase, step-by-step blueprint for planning, designing, visualizing, and delivering compelling data storytelling in business presentations. Following her blueprint, you will learn how to use neuroscience and cinematic storytelling techniques to galvanize your stakeholders into action. By the final page, you'll know exactly how to: Choose the data that matters most to your decision-makers Speak to different stakeholder audience personality types (even the most challenging) Infuse your data presentation with a persuasive narrative storyline Craft strategic recommendations that get approved and implemented Design simple, stunning slides that communicate without confusing Transmit your data story with best-practice data visualization techniques Avoid the most common data visualization violations and charting pitfalls Prepare for and deliver your presentation like a professional speaker Navigate challenging meeting conversations and logistics with easeWhether you work with little or big data, this book will show you how to prevent presentation zombies and inspire the action and credibility you and your organization deserve
Keywords: Business presentations